Multi-criteria decision-making for the life cycle of sustainable high pressure die casting products - Pagone, Emanuele; Papanikolaou, Michail; Salonitis, Konstantinos; Jolly, Mark R. (Inderscience, 2020)
Although a significant body of literature has been devoted to establish metrics capable of measuring the performance of manufacturing systems (including foundries) and their influence on decision-making, there is a scarcity of comprehensive and organic studies on performance indicators encompassing sustainability. The objective of this investigation is the selection of the most suitable material for the manufacture of an automotive component using the High Pressure Die Casting (HPDC) process. The performance of three different alloys (Aluminium-A380, Magnesium-AZ91D and Zinc-ZA8) was evaluated based on four different classes of metrics, namely: (a) cost, (b) time, (c) quality and (d) sustainability. The metrics selected refer to the overall product life cycle and process characteristics and have been normalised by mass to extend the applicability of the selection method to parts produced with similar process and design specifications but different mass. The deterministic TOPSIS method has been adopted to weigh and combine the different metrics used and drive the decision making process. According to the results, although the zinc alloy appears to be the most expensive option, it should be favoured over the two alternatives due to its significantly superior performance with respect to the quality and sustainability criteria. The current investigation demonstrates that the implementation of the TOPSIS method in combination with the added sustainability dimension influences the decision making process and challenges well-established decision making trends in the automotive industry during the past few decades.
Keywords: Automotive products; Key Performance Indicators (KPIs); sustainability metrics; Foundries; manufacturing systems; lifecycle analysis; Multi Criteria Decision Making (MCDM); sustainable development; High Pressure Die Casting (HPDC)